Students' progress in the University of the Philippines - Sarayba, Virginia G. 1929- (University of the Philippines], 1955)
A factual picture of the students in the University of the Philippines today (at the conduct of the study) and how they fared within the university-fold are presented through a direct appraisal of the students' scholastic records pertaining to the length of their stay in their respective colleges, the number of students who drop out in college, the subjects in which majority of the students fail and those who finish as scholars and graduates with honors regardless of whether or not they are admitted as scholars.